2006
DOI: 10.1182/blood-2006-01-010199
|View full text |Cite
|
Sign up to set email alerts
|

Unique effects of Stat3 on the early phase of hematopoietic stem cell regeneration

Abstract: IntroductionHematopoietic stem cells (HSCs) constitute a rare subpopulation in hematopoietic tissues and are uniquely defined by their ability to divide many times with full retention of their pluripotentiality. 1 This self-renewal function underlies the ability of HSCs to produce new blood cells throughout the life of the individual. It also allows them to regenerate the entire blood-forming system in vivo, including the HSC compartment, following their transplantation into irradiated recipients. 2,3 In mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 41 publications
(54 reference statements)
4
77
1
1
Order By: Relevance
“…Repopulation of transplanted cells in the recipients was assessed by flow cytometry to measure the proportion of leukocytes expressing the donor-origin (Ly5.2) surface antigen in their blood or bone marrow. The lineages of repopulated hematopoietic cells were analyzed by staining with anti-Mac-1 (BD Pharmingen, San Diego), anti-Gr-1 antibody (BD Pharmingen) for myeloid cells, and anti-B220 antibodies (BD Pharmingen) for lymphoid engraftment, as described previously [26]. For quantitative measurements of HSC numbers, competitive repopulating unit (CRU) assays were performed as previously described [27].…”
Section: Methodsmentioning
confidence: 99%
“…Repopulation of transplanted cells in the recipients was assessed by flow cytometry to measure the proportion of leukocytes expressing the donor-origin (Ly5.2) surface antigen in their blood or bone marrow. The lineages of repopulated hematopoietic cells were analyzed by staining with anti-Mac-1 (BD Pharmingen, San Diego), anti-Gr-1 antibody (BD Pharmingen) for myeloid cells, and anti-B220 antibodies (BD Pharmingen) for lymphoid engraftment, as described previously [26]. For quantitative measurements of HSC numbers, competitive repopulating unit (CRU) assays were performed as previously described [27].…”
Section: Methodsmentioning
confidence: 99%
“…These include regulators of the cell cycle, such as Cdkn1a (p21) 13 and Cdkn2c (p18) 14 and members of the transcriptional control machinery, such as HoxA9, 15 HoxB4, 16 Phc1 (Rae28), 17 Bmi1, 18 Ezh2, 19 Gfi1, 20 Gata2 21 and Gata3, 22 Etv6, 23 Pcgf2 (Mel18), 24 Mcl1, 25 Meis1, 15 and Runx1. 21 In addition, growth factor receptors, such as GP130 26 and KIT, 27 and signaling factors, such as STAT3, 28 STAT5, 29 PTEN, 30 and LNK, 11 have been shown to affect the ability of HSCs to execute self-renewal divisions. These findings reinforce data suggesting that multiple external cues, including Steel factor (SF), 31 thrombopoietin, 32,33 transforming growth factor-␤, 34 flt3-ligand, 35 and factors, such as interleukin-6 (IL-6) and IL-11, 36,37 which signal through GP130, can modulate HSC self-renewal, proliferation, and viability independently.…”
Section: Introductionmentioning
confidence: 99%
“…Gain and loss of function studies have shown that both Stat5 and Stat3 are positive regulators of HSC self-renewal. 63,64 In addition to transcription factors, other proteins involved in the modulation of gene expression have been found to regulate self-renewal of HSCs. Bmi-1 is a polycomb group (PcG) protein that forms the Polycomb repression complex 1 (PRC1)with other members of the PcG family, such as 65 The mechanisms whereby Bmi-1 and its protein complex maintains HSC self-renewal are unclear, but it may be attributed to the repression of p16 and p19, and/or repression of differentiation-related gene expression programs.…”
Section: Molecular Mechanisms Regulating Hsc Self-renewalmentioning
confidence: 99%